Counseling Intervention to Reduce Violence and Promote the Psychosocial Well- Being of Women Who Experience Domestic Violence - Maha Mowafy1 , Dina Shorkry2 , Heba El Nahas3 , Asmaa Sayed4 , Arwa El Shafei5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: This study aims to review married women with domestic violence and detecting the effectiveness of counseling intervention on the reduction of intimate partner violence (IPV). Methods: Phase one of this study was a cross-sectional in which 315 married women living in Al-Badrashin, a slum area in Giza-Egypt, were included and invited to participate in the study and screened for IPV, social support, and psychological status; phase two was an interventional phase in which all abused women detected in phase one invited to participate in the interventional counseling program. Results: The study revealed that the overall prevalence of IPV among the studied group was (37.7%); the highest form (54.0%) was psychological abuse, followed by physical (52%) one then severe combined abuse including sexual abuse items (48.6%). However; less than one fourth (22.2%) were exposed to harassment. Also revealed the presence of high significant p-value (0.000) reductions in all forms of violence following the intervention program. Conclusions: Counseling intervention had a positive effect on participants, demonstrating a decrease in violence exposure, improvement of social support and psychological status.